Rice as an Early form of Money in the Economic Sense: Satisfying Store of Value, Unit of Account and Medium of Exchange Requirements - Paul F. Gentle (SocioEconomic Challenges)
This article examines the special case of rice in different parts of the World, as it was used for an additional purpose, besides providing for nutritional needs of people. When confidence in a system of currency with coins is present, this more conventional form of money takes precedence. A respected economic form of currency which may include paper and coins or accounts thereof, has all three elements of money: a medium of exchange, a store of value and as a unit of account. In this article, the concept of value includes subjective value, what people have in terms of pleasure and displeasure in regard to owning and seeing a particular object. This article shows that rice satisfied the three requirements for serving as a form of money, at some time periods and in some areas of the World. It has been found that rice met the three criteria necessary for them to be a type of money, in history in different countries. Some examples include certain past time periods in parts of Indonesia, Greece, North America, Japan, and some other places. Although rice was later found to not work as well, compared to some other specific forms of money. Understanding how different forms of money appear and then are replaced by other forms of money is important in the quest to understand what exactly money is. Monetary theory concepts concerning Gresham’s Law and the Quantity Theory of Money are discussed in regard to using rice as money.